ISOLASI MINYAK ATSIRI BIJI BUAH PALA (Myristica fragrans Houtt) DAN PENGGUNAANNYA DALAM PEMBUATAN SABUN TRANSPARAN YANG DI KOMBINASIKAN DENGAN MINYAK JARAK - Yuniarti, Rafita; Lubis, Minda Sari; Anggraini, Dea Puspa (Jurnal Farmanesia, 2019)
Nutmeg oil is an essential oil produced through the distillation process from dried nutmeg seeds. Nutmeg oil is usually obtained after the fat contained in it is removed first. Nutmeg oil is used in the pharmaceutical industry as a remedy for stomach aches and diarrhea. The development of castor oil in Indonesia has been increasingly widespread, but its utilization has not been maximized. To maximize the utilization of castor oil, castor oil is processed into soap. Castor oil is always used in the manufacture of transparent soap because castor oil can provide transparent properties to soap. Soap is a surfactant that is used with water for cleaning and washing. The purpose of this study was to use nutmeg essential oil as a comparison with castor oil in making transparent soap. The research method used is experimental. Making transparent soap using nutmeg essential oil as a comparison with castor oil, the amount of nutmeg essential oil and castor oil used was 5ml, 10ml, 15ml, 20ml. Tests of soap preparations made include organoleptic tests, water content tests, pH tests, mineral oil tests, high foam tests and free fatty acid/free alkali tests. From the results of the tests carried out, it can be concluded that the ratio of nutmeg oil and castor oil which has the best concentration is the concentration of 5ml jatropha: 15ml nutmeg. This comparison meets the requirements, namely the results of organoleptic tests that produce good shape, smell and color, the results of the water content test produce 5.5%, the pH test results produce 8. the mineral oil test results were negative, the foaming power and foam stability test results were fixed at 285 and the free alkali test results were 0.039